Kartogenin Improves Osteogenesis of Bone Marrow Mesenchymal Stem Cells via Autophagy - Huichun Yan; Tingting Yu; Jing Li; Ting Zhang; Qian Li; Yanheng Zhou; Dawei Liu (Hindawi Limited, 2022)
Kartogenin (KGN), a novel small-molecule compound, has been considered a promising chondrogenic promoter in cartilage regeneration. However, whether KGN also participates in osteogenesis and bone regeneration remains unclear. This research was designed to explore the roles of KGN on osteogenic differentiation in bone marrow mesenchymal stem cells (BMMSCs) as well as determine the possible mechanism of osteogenesis. We revealed that KGN enhanced the osteogenic differentiation capacity of BMMSCs without affecting cell proliferation, during which autophagic activities and the expression of autophagy-related genes were promoted. Moreover, KGN upregulated the phosphorylation level of the Smad1/5/9 signaling, and inhibition and activation of Smad signaling were also applied to validate the involvement of Smad in BMMSCs during KGN treatment. In summary, this study shows that KGN promotes osteogenic differentiation of BMMSCs through enhancing autophagic levels and upregulating Smad1/5/9 signaling mechanically.